Analisis laras bahasa kesihatan dalam akhbar atas talian al-Jazeera / Noor Shahida Wahab - Noor Shahida, Wahab (2016)
A research of health's register in al-Jazeera.net newspaper is an example of research in the field of sociolinguistics. It contains specific terms that are often used in the writings as well as a large number of borrowings from other languages that have been adapted to the language borrowed. This study aimed at identifying the specific terms of health grammar used in the paper and determine its frequency. It also seeks to explain the loan terms contained in it and make the analysis of morphophonology to explain the changes involved. This qualitative research involved 15 health news articles from newspaper al- Jazeera.net on-line. The election of the news related with cancer is drawn from archival sources during the month of May 2015. Theory of Leech & Short (1981) were used as the theoretical framework and research approach supported by S. Nathesan (1995). The findings were discussed descriptively and presented in tables and pie charts. The study found that the language certainly has a health specific terms used in writing health articles as well as the use of terms that are directly related to it including the health grammar. A few morphological and phonological changes happened when Arabic language adapted the loanwords.